Market Liberalism and Social Protection: Hayek, Durkheim and Polanyi in Theoretical Perspective - Akturk, Sener (Journal of Academic Studies, 2002)
Examines the views of neoclassicist Friedrich A. Hayek, sociologist Emile Durkheim and Karl Polanyi on liberalism. Relationship between the individual, the market economy and society; Features of Hayekian neoclassical economics; Information on Polanyi's book 'The Great Transformation.'
Political Science
Keywords: DURKHEIM; Emile; Great Transformation; The (Book); HAYEK; Friedrich A. von (Friedrich August); 1899-1992; liberalism; social protection

Between Aristotle and the Welfare State: The Establishment, Enforcement, and Transformation of the Moral Economy in Karl Polanyi's The Great Transformation - Akturk, Sener (Theoria: A Journal of Social & Political Theory, 2006)
The article examines the transformation of the moral economy in the book "The Great Transformation," by Karl Polyani. Polyani's work has been criticized for having an anti-democratic, Aristotelian, and aristocratic undertones. However, the author claimed that it has been misinterpreted and a communitarian-liberal debate has been brought to clarify the nature of moral economy.
Political Science
Keywords: Great Transformation; The (Book); criticism; democracy; economic policy